2018
DOI: 10.1038/s41598-018-35870-x
|View full text |Cite
|
Sign up to set email alerts
|

Tuning structure and mechanical properties of Ta-C coatings by N-alloying and vacancy population

Abstract: Tailoring mechanical properties of transition metal carbides by substituting carbon with nitrogen atoms is a highly interesting approach, as thereby the bonding state changes towards a more metallic like character and thus ductility can be increased. Based on ab initio calculations we could prove experimentally, that up to a nitrogen content of about 68% on the non-metallic sublattice, Ta-C-N crystals prevail a face centered cubic structure for sputter deposited thin films. The cubic structure is partly stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…However, refractory ceramics typically possess only one or the other. In investigations designed to address the physics behind the long-standing challenge of realizing simultaneously high strength and high ductility in ceramics films, electronic structure results have shown that VEC is an important parameter for predicting mechanical properties in TM nitride alloys [54,60,98,101,105,107,108,117]. The overall results demonstrate that hardness decreases (maximum hardness is expected at VEC ~ 8.4), while ductility increases with increasing VEC; and optimum toughness is predicted for alloys with VEC ~ 10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, refractory ceramics typically possess only one or the other. In investigations designed to address the physics behind the long-standing challenge of realizing simultaneously high strength and high ductility in ceramics films, electronic structure results have shown that VEC is an important parameter for predicting mechanical properties in TM nitride alloys [54,60,98,101,105,107,108,117]. The overall results demonstrate that hardness decreases (maximum hardness is expected at VEC ~ 8.4), while ductility increases with increasing VEC; and optimum toughness is predicted for alloys with VEC ~ 10.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach to increasing toughness, but also based upon VEC, was proposed by Glechner et al [117]. In this DFT-based work, instead of tuning the number of valence electrons by alloying the TM sublattice, they used TaC1-xNx as a model system to investigate alloying on the non-metal anion sublattice and found that both the hardness and elastic modulus of cubic TaC1-xNx decreases with increasing N content (i.e., with increasing VEC), which they attributed primarily to changes in bonding leading toward a more metallic character.…”
Section: The Quest For High Toughness In Ceramic Filmsmentioning
confidence: 99%
“…Additionally, an enormous versatility in structural and mechanical properties can be accomplished by intentionally using the typically unwanted products of Physical Vapour Deposition (PVD) processes: vacancies and point defects in general [16][17][18][19][20][21] . Recent work by Buchinger et al 22 particularly underlined the important role of theory-guided defect design, showing an impressive fracture toughness enhancement in TiN/WN x superlattices, 4.6 MPa √ m for Λ = 10 nm, which presents one of the highest records among transition metal nitrides.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of the aerospace and marine industries, ultrahigh temperature ceramics (UHTCs) have been and continue to be the most widely used multifunctional materials due to their high strength, good fracture toughness, and excellent resistance to oxidation. , As a subset of UHTCs, transition metal carbides possess a high melting point; for example, the melting points of TiC, ZrC, NbC, VC, and HfC are 3373 K, 3805 K, 3883 K, 3083 K, and 4232 K, respectively. The TaC ceramics, as a vital member of the transition metal carbides (TMCs), have widely been used in refractories, abrasives, cutting tools, and coating materials . However, the hardness and fracture toughness of TaC ceramics show tremendous variations at different preparation conditions and diverse processing methods.…”
Section: Introductionmentioning
confidence: 99%